Three-dimensional structure ceramic-polymer composite solid electrolyte and preparation method thereof
By combining the three-dimensional structural ceramics with polymer composites, a three-dimensional structural ceramic-polymer composite solid electrolyte is solved, and the problems of low ionic conductivity and poor interface contact of solid electrolytes are achieved, and high ionic conductivity and good mechanical stability are achieved.
Patent Information
- Application Number
- CN202411811426.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing solid electrolyte has a low ionic conductivity, and the contact state between the inorganic solid electrolyte and the electrode sheet is poor, which affects the charging and discharging performance of the battery.
Three-dimensional structural ceramic-polymer composite solid electrolyte is used to regulate the formation of ceramic-based or polymer-based solid electrolytes by compounding the three-dimensional structural ceramics with polymer composites, and improve the interface contact state between inorganic substances and polymers.
It significantly improves the ionic conductivity of solid electrolytes, improves interface contact problems, improves the charging and discharging performance of the battery, and improves the mechanical stability of the material.
Smart Images

Figure CN119627185A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery solid electrolytes, and specifically relates to a three-dimensional structured ceramic-polymer composite solid electrolyte and a preparation method thereof. Background Art
[0002] With the advent of the human energy crisis and the improvement of environmental protection awareness, new energy vehicles have received unprecedented attention. However, the existing liquid lithium-ion batteries are prone to fire and explosion due to the use of liquid organic electrolytes, and their safety has not been completely solved. At the same time, the energy density of existing liquid lithium-ion batteries has reached its upper limit and cannot be further improved, resulting in the problem of the endurance of new energy vehicles. Solid-state batteries, due to the absence of liquid electrolytes, have significantly improved safety and greatly increased energy density, and are the mainstream direction of the development of secondary lithium-ion batteries in the future.
[0003] Existing solid electrolytes are mainly divided into polymer solid electrolytes and inorganic solid electrolytes. Polymer solid electrolytes have the advantages of good flexibility, low cost, and easy large-scale processing and molding, but their very low room temperature ionic conductivity limits their application. Inorganic solid electrolytes include oxide solid electrolytes, sulfide solid electrolytes, and halide electrolytes. Among them, oxide solid electrolytes have high chemical stability, high electrochemical stability, good mechanical strength, and high electrochemical oxidation potential. However, since the contact between the inorganic solid electrolyte and the pole piece is solid-solid contact, especially the oxide has very high rigidity, the contact state with the positive and negative electrodes is very poor, and it is easy to change from surface contact to point contact during the charge and discharge process, which seriously affects the charge and discharge performance of the battery. At the same time, due to the rigid structure of the oxide, the electrolyte membrane cannot be prepared on a large scale, and it needs to be composited before it can be used. Therefore, the composite of polymer solid electrolytes and inorganic solid electrolytes has received widespread attention. The composite of the two can not only solve the problem of low ionic conductivity of polymer solid electrolytes, but also solve the problem of insufficient structural toughness of inorganic solid electrolytes, and significantly improve the interface contact problem. Summary of the invention
[0004] One of the purposes of the present invention is to provide a three-dimensional structured ceramic-polymer composite solid electrolyte to solve the problem of low ion conductivity of solid electrolytes;
[0005] The second object of the present invention is to provide a method for preparing a three-dimensional structured ceramic-polymer composite solid electrolyte to improve the problem of interface contact between the polymer solid electrolyte and the inorganic solid electrolyte.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] In a first aspect, a three-dimensional structural ceramic-polymer composite solid electrolyte comprises a three-dimensional structural ceramic and a polymer composite;
[0008] The three-dimensional structural ceramic is an oxide-type ceramic electrolyte with a three-dimensional structure, and the ceramic electrolyte is one of LLTO (lithium lanthanum titanium oxide) ceramic, LLZO (lithium lanthanum zirconium oxide) ceramic and LATP (lithium aluminum titanium phosphate) ceramic;
[0009] The polymer composite includes a polymer, a lithium salt, nitriles and a phenoxy resin.
[0010] Furthermore, the polymer includes one or more of polyethylene oxide, polyvinylidene fluoride, polymethyl methacrylate, polyvinylidene fluoride-co-hexafluoropropylene, polyurethane acrylate, and polyethylene glycol.
[0011] Furthermore, the lithium salt includes lithium halide (LiX, X = F, Cl, Br, I), lithium bis (trifluoromethylsulfonyl) imide (LiTFSI), lithium perchlorate (LiClO 4 ), lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ) or both.
[0012] Furthermore, the nitriles include one or two of succinonitrile, adiponitrile and benzyl cyanide.
[0013] In a second aspect, a method for preparing a three-dimensional structured ceramic-polymer composite solid electrolyte comprises the following steps:
[0014] S1: The composite slurry of ceramic electrolyte and epoxy resin is coated to obtain a film;
[0015] S2: stamping the adhesive film to obtain a stamped adhesive film;
[0016] S3: sintering the imprinted film to obtain a three-dimensional structural ceramic;
[0017] S4: preparing a polymer composite system solution, and blending it with three-dimensional structural ceramics to obtain a three-dimensional structural ceramic-polymer composite solid electrolyte.
[0018] Furthermore, the mass ratio of the ceramic electrolyte to the epoxy resin in S1 is (5-15):(2.5-30).
[0019] Furthermore, the epoxy resin in S1 is a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin in a mass ratio of (2-20): (0.5-10).
[0020] Furthermore, the epoxy value of the bisphenol A epoxy resin is 0.001-0.5, and preferably, the epoxy value of the bisphenol A epoxy resin is 0.02-0.09.
[0021] Furthermore, the coating process in S1 is specifically as follows: using PET with a thickness of 50 μm as a substrate (base film), coating the composite slurry of ceramic electrolyte and epoxy resin onto the substrate through a slit, drying to obtain a composite adhesive film, and peeling off the substrate to obtain an adhesive film.
[0022] Furthermore, the thickness of the adhesive film is 10-100 μm, and preferably, the thickness of the adhesive film is 20-50 μm.
[0023] Furthermore, the S1 further includes:
[0024] S1-1: preparing oxygen ceramic electrolyte slurry: dissolving ceramic electrolyte in a solvent and crushing to obtain ceramic electrolyte slurry; the crushing method includes but is not limited to high-energy ball milling or sand milling;
[0025] S1-2: preparing a composite slurry of ceramic electrolyte and epoxy resin: uniformly mixing the ceramic electrolyte slurry and the epoxy resin to obtain a composite slurry of ceramic electrolyte and epoxy resin.
[0026] Furthermore, in S2, the stamping template is a metal nickel template having regularly shaped protrusions on the surface; the shapes of the protrusions include but are not limited to hexagons, triangles, quadrilaterals or circles.
[0027] Furthermore, the height of the protrusion is 10-50 μm, and preferably, the height of the protrusion is 10-20 μm; the pitch of the protrusion is 5-20 μm, and preferably, the height of the protrusion is 5-10 μm.
[0028] Furthermore, in S2, the stamping temperature is 30-100° C., preferably, the stamping temperature is 30-60° C.; the stamping speed is 1-20 cm / min, preferably, the stamping speed is 1-5 cm / min.
[0029] Furthermore, in S3, the sintering temperature is 500-950° C., and the sintering time is 1-10 h.
[0030] Furthermore, in S4, the polymer composite system solution is prepared by the following steps: dissolving the polymer, lithium salt, nitrile and phenoxy resin in a solvent in a mass ratio of (30-50): (10-25): (10-20): (1-5), mixing them evenly, and obtaining a polymer composite system solution.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The present invention provides a three-dimensional structured ceramic-polymer composite solid electrolyte and a preparation method thereof. By compounding the three-dimensional structured ceramic with the polymer composite, it is possible to very simply and effectively control the formation of a ceramic-based or polymer-based solid electrolyte, significantly improving the interface contact state between the inorganic substance and the polymer, with high ionic conductivity. The phenoxy resin can significantly improve the toughness of the material and has high mechanical stability.
[0033] 2. The present invention grinds the ceramic electrolyte into micro-nano particles, mixes and coats them with epoxy resin, and can obtain a ceramic electrolyte / epoxy resin film with controllable thickness. By adjusting the type of bisphenol A epoxy resin and the ratio of bisphenol F epoxy resin in the epoxy resin, the film can be in a solid structure at room temperature (25-30°C) and can be smoothly reeled and unwound. At the same time, since epoxy resin can very well infiltrate inorganic particles, the epoxy resin and ceramic particles in the dried film can fully wrap each other.
[0034] 3. Through the imprinting method, the ceramic electrolyte / epoxy resin film can be imprinted in a controlled manner, and the pattern of the template can be replicated on the film surface to form regular and controllable holes. Combined with the sintering process, a three-dimensional ceramic electrolyte skeleton with regular holes can be formed. This rich three-dimensional skeleton is conducive to the subsequent filling of polymer solutions to form a ceramic / polymer composite electrolyte with close contact. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The present invention will be further described below in conjunction with the accompanying drawings.
[0036] Figure 1 It is a schematic diagram of the preparation process of a three-dimensional structure ceramic-polymer composite solid electrolyte of the present invention;
[0037] Figure 2 is an impedance spectrum of the three-dimensional structured ceramic-polymer composite solid electrolyte prepared in Example 1 of the present invention;
[0038] Figure 3 is a linear sweep voltammetric curve of the three-dimensional structure ceramic-polymer composite solid electrolyte prepared in Example 1 of the present invention;
[0039] Figure 4 It is a stress-strain curve diagram of the three-dimensional structure ceramic-polymer composite solid electrolyte prepared by Example 1 of the present invention. DETAILED DESCRIPTION
[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] In the present invention, there is no special requirement for the drying process of the coating process. Without violating the inventive concept of the present application, any known drying process can be used in the present application. It can be carried out by electric heating, infrared heating, blast heating, etc. It is understandable that the relevant process parameters such as drying temperature and drying time of the present application are not particularly limited. Without violating the inventive concept of the present application, any technical solution obtained by adjusting the parameters without creative labor is within the protection scope of the present application.
[0042] Please refer to the schematic diagram of the preparation process of the three-dimensional structure ceramic-polymer composite solid electrolyte in the following embodiment. Figure 1 .
[0043] Example 1
[0044] A method for preparing a three-dimensional structured ceramic-polymer composite solid electrolyte comprises the following steps:
[0045] S1: Preparation of adhesive film:
[0046] S1-1: 10 g LLTO was dissolved in 20 g xylene by ball milling for 5 h at a rotation speed of 500 rpm to obtain LLTO slurry with a D50 of 500 nm;
[0047] S1-2: Add 2 g of bisphenol A epoxy resin E-06 and 0.5 g of bisphenol F epoxy resin 830 to the LLTO slurry, and stir at a high speed of 1000 rpm for 0.5 h to obtain a composite slurry of ceramic electrolyte and epoxy resin;
[0048] S1-3: Using PET with a thickness of 50 μm as a substrate (base film), a composite slurry of ceramic electrolyte and epoxy resin is coated onto the substrate through a slit at a coating speed of 3 m / min, and dried at 100°C to obtain a composite adhesive film. The substrate is peeled off to obtain an adhesive film with a thickness of 20 μm;
[0049] S2: Design the shape of the protrusions on the metal nickel template to be hexagonal, the height of the template protrusions is 50 μm, the pitch of the protrusions is 5 μm, and the film is embossed at a temperature of 30° C. and a speed of 20 cm / min. The template is peeled off to obtain an embossed film;
[0050] S3: placing the imprinted film in a muffle furnace for sintering at a temperature of 500°C for 10 hours to obtain a three-dimensional structural ceramic;
[0051] S4: Polyethylene oxide, LiTFSI, succinonitrile and phenyl resin PKHH are weighed in a mass ratio of 50:25:10:1; polyethylene oxide, LiTFSI and succinonitrile are dissolved in 30 g of xylene, and phenyl resin PKHH is dissolved in 15 g of butanone in advance, and the two are mixed evenly to obtain a polymer composite system solution; 2 g of three-dimensional structural ceramics is fully immersed in the polymer composite system solution, taken out after 5 hours, and excess solution on the surface is absorbed with filter paper, placed at room temperature for 24 hours, and continued to dry in an oven at 50°C for 24 hours to obtain a three-dimensional structural ceramic-polymer composite solid electrolyte.
[0052] After weighing, the mass of the three-dimensional structural ceramic-polymer composite solid electrolyte obtained after drying is 12±0.01g; calculation shows that the mass ratio of the three-dimensional structural ceramic to the polymer composite is 2:10, and this material is a typical three-dimensional structural ceramic-polymer composite solid electrolyte.
[0053] Example 2
[0054] A method for preparing a three-dimensional structured ceramic-polymer composite solid electrolyte comprises the following steps:
[0055] S1: Preparation of adhesive film:
[0056] S1-1: 15 g LLTO was dissolved in 25 g xylene by ball milling for 5 h at a rotation speed of 1000 rpm to obtain LLTO slurry with a D50 of 300 nm;
[0057] S1-2: Add 5 g of bisphenol A epoxy resin E-06 and 1 g of bisphenol F epoxy resin 830 to the LLTO slurry, and stir at a high speed of 1000 rpm for 0.5 h to obtain a composite slurry of ceramic electrolyte and epoxy resin;
[0058] S1-3: Using PET with a thickness of 50 μm as a substrate (base film), a composite slurry of ceramic electrolyte and epoxy resin is coated onto the substrate through a slit, the coating speed is 1 m / min, and dried at 80°C to obtain a composite adhesive film, and the substrate is peeled off to obtain an adhesive film with a thickness of 50 μm;
[0059] S2: Design the shape of the protrusions on the metal nickel template to be hexagonal, the height of the template protrusions is 40 μm, the pitch of the protrusions is 10 μm, and the film is embossed at a temperature of 50° C. and a speed of 10 cm / min. The template is peeled off to obtain an embossed film;
[0060] S3: placing the imprinted film in a muffle furnace for sintering at a temperature of 950°C for 1 hour to obtain a three-dimensional structural ceramic;
[0061] S4: polyvinylidene fluoride, LiTFSI, succinonitrile and phenyl resin PKHB are weighed in a mass ratio of 30:20:10:5; polyvinylidene fluoride, LiTFSI and succinonitrile are dissolved in 25g of xylene, and phenyl resin PKHB is dissolved in 10g of butanone in advance, and the two are mixed evenly to obtain a polymer composite system solution, and 5g of three-dimensional structural ceramics are fully immersed in the polymer composite system solution, taken out after 10 hours, and excess solution on the surface is absorbed with filter paper, and placed at room temperature for 24 hours, and continued to dry in an oven at 50°C for 24 hours to obtain a three-dimensional structural ceramic-polymer composite solid electrolyte.
[0062] After weighing, the mass of the three-dimensional structural ceramic-polymer composite solid electrolyte obtained after drying is 7.14±0.01g; calculation shows that the mass ratio of the three-dimensional structural ceramic to the polymer composite is 7:3, and this material is a typical three-dimensional structural ceramic-polymer composite solid electrolyte.
[0063] Example 3
[0064] A method for preparing a three-dimensional structured ceramic-polymer composite solid electrolyte comprises the following steps:
[0065] S1: Preparation of adhesive film:
[0066] S1-1: 10 g LLTO was dissolved in 15 g toluene by sand milling, and the mixture was ball milled for 15 h at a speed of 1500 rpm to obtain an LLTO slurry with a D50 of 150 nm;
[0067] S1-2: Add 20 g of bisphenol A epoxy resin E-06 and 10 g of bisphenol F epoxy resin 830 to the LLTO slurry, and stir at a high speed of 1000 rpm for 0.5 h to obtain a composite slurry of ceramic electrolyte and epoxy resin;
[0068] S1-3: Using PET with a thickness of 50 μm as a substrate (base film), a composite slurry of ceramic electrolyte and epoxy resin is coated onto the substrate through a slit, the coating speed is 3 m / min, and dried at 60°C to obtain a composite adhesive film, and the substrate is peeled off to obtain an adhesive film with a thickness of 50 μm;
[0069] S2: Design the shape of the protrusions on the metal nickel template to be a quadrilateral, the height of the template protrusions is 50 μm, the pitch of the protrusions is 15 μm, and the film is embossed at an embossing temperature of 80°C and an embossing speed of 10 cm / min. The template is peeled off to obtain an embossed film;
[0070] S3: placing the imprinted film in a muffle furnace for sintering at a temperature of 750°C for 5 hours to obtain a three-dimensional structural ceramic;
[0071] S4: Polymethyl methacrylate, lithium perchlorate, succinonitrile and phenyl resin PKHH are weighed in a mass ratio of 50:10:25:5; polymethyl methacrylate, lithium perchlorate and succinonitrile are dissolved in 45g of xylene, and phenyl resin PKHH is dissolved in 25g of butanone in advance, and the two are mixed evenly to obtain a polymer composite system solution, and 5g of three-dimensional structural ceramics are fully immersed in the polymer composite system solution, taken out after 5h, and excess solution on the surface is absorbed with filter paper, and placed at room temperature for 24h, and continued to dry in an oven at 50°C for 24h to obtain a three-dimensional structural ceramic-polymer composite solid electrolyte.
[0072] After weighing, the mass of the three-dimensional structural ceramic-polymer composite solid electrolyte obtained after drying is 105±0.01g; calculation shows that the mass ratio of the three-dimensional structural ceramic to the polymer composite is 0.5:10, and this material is a typical three-dimensional structural ceramic-polymer composite solid electrolyte.
[0073] Example 4
[0074] A method for preparing a three-dimensional structured ceramic-polymer composite solid electrolyte comprises the following steps:
[0075] S1: Preparation of adhesive film:
[0076] S1-1: 10 g of LATP was dissolved in 30 g of xylene by ball milling for 5 h at a speed of 2000 rpm to obtain a LATP slurry with a D50 of 800 nm;
[0077] S1-2: Add 10 g of bisphenol A epoxy resin E-06 and 0.5 g of bisphenol F epoxy resin 830 to the LATP slurry, and stir at a high speed of 1000 rpm for 0.5 h to obtain a composite slurry of ceramic electrolyte and epoxy resin;
[0078] S1-3: Using PET with a thickness of 50 μm as a substrate (base film), a composite slurry of ceramic electrolyte and epoxy resin is coated onto the substrate through a slit, the coating speed is 3 m / min, and dried at 100°C to obtain a composite adhesive film, and the substrate is peeled off to obtain an adhesive film with a thickness of 30 μm;
[0079] S2: Design the shape of the protrusions on the metal nickel template to be hexagonal, the height of the template protrusions is 25 μm, the protrusion spacing is 5 μm, and the film is embossed at a temperature of 100° C. and a speed of 20 cm / min. Peel off the template to obtain an embossed film;
[0080] S3: placing the imprinted film in a muffle furnace for sintering at a temperature of 750°C for 5 hours to obtain a three-dimensional structural ceramic;
[0081] S4: polyvinylidene fluoride co-hexafluoropropylene, lithium hexafluorophosphate, benzyl nitrile and phenyl resin PKHB are weighed in a mass ratio of 30:10:10:3; polyvinylidene fluoride co-hexafluoropropylene, lithium hexafluorophosphate and benzyl nitrile are dissolved in 40g of xylene, and phenyl resin PKHB is dissolved in 25g of butanone in advance, and the two are mixed evenly to obtain a polymer composite system solution, and 10g of three-dimensional structural ceramics are fully immersed in the polymer composite system solution, taken out after 1 hour, and excess solution on the surface is absorbed with filter paper, and placed at room temperature for 24 hours, and continued to dry in an oven at 50°C for 24 hours to obtain a three-dimensional structural ceramic-polymer composite solid electrolyte.
[0082] After weighing, the mass of the three-dimensional structural ceramic-polymer composite solid electrolyte obtained after drying is 12±0.01g; calculation shows that the mass ratio of the three-dimensional structural ceramic to the polymer composite is 10:2, and this material is a typical three-dimensional structural ceramic-polymer composite solid electrolyte.
[0083] Example 5
[0084] A method for preparing a three-dimensional structured ceramic-polymer composite solid electrolyte comprises the following steps:
[0085] S1: Preparation of adhesive film:
[0086] S1-1: 5 g of LLTO was dissolved in 20 g of xylene by sand milling, and the mixture was ball milled for 5 h at a speed of 500 rpm to obtain an LLTO slurry with a D50 of 500 nm;
[0087] S1-2: Add 2 g of bisphenol A epoxy resin E-51 and 1 g of bisphenol F epoxy resin 830 to the LLTO slurry, and stir at a high speed of 1000 rpm for 0.5 h to obtain a composite slurry of ceramic electrolyte and epoxy resin;
[0088] S1-3: Using PET with a thickness of 50 μm as a substrate (base film), a composite slurry of ceramic electrolyte and epoxy resin is coated onto the substrate through a slit at a coating speed of 2.5 m / min, and dried at 40°C to obtain a composite adhesive film. The substrate is peeled off to obtain an adhesive film with a thickness of 30 μm;
[0089] S2: Design the shape of the protrusions on the metal nickel template to be hexagonal, the height of the template protrusions is 30 μm, the pitch of the protrusions is 20 μm, and the film is embossed at a temperature of 30° C. and a speed of 15 cm / min. The template is peeled off to obtain an embossed film;
[0090] S3: placing the imprinted film in a muffle furnace for sintering at a temperature of 650°C for 3 hours to obtain a three-dimensional structural ceramic;
[0091] S4: Polyethylene oxide, lithium fluoride, benzyl cyanide and phenyl resin PKHH are weighed in a mass ratio of 45:25:10:5; polyethylene oxide, lithium fluoride and benzyl cyanide are dissolved in 25 g of tetrahydrofuran, and phenyl resin PKHH is dissolved in 25 g of butanone in advance, and the two are mixed evenly to obtain a polymer composite system solution, and 1 g of three-dimensional structural ceramics is fully immersed in the polymer composite system solution, taken out after 15 hours, and excess solution on the surface is absorbed with filter paper, and placed at room temperature for 24 hours, and continued to dry in an oven at 50°C for 24 hours to obtain a three-dimensional structural ceramic-polymer composite solid electrolyte.
[0092] After weighing, the mass of the three-dimensional structural ceramic-polymer composite solid electrolyte obtained after drying is 11±0.01g; calculation shows that the mass ratio of the three-dimensional structural ceramic to the polymer composite is 1:10, and this material is a typical three-dimensional structural ceramic-polymer composite solid electrolyte.
[0093] Comparative Example 1
[0094] The difference between this comparative example and Example 1 is that the adhesive film obtained in S1-3 is not subjected to the S2 imprinting process but is directly sintered, and the other steps and parameters remain the same.
[0095] Comparative Example 2
[0096] The difference between this comparative example and Example 1 is that no phenyl resin PKHH is added to the polymer composite system in S4, and the other steps and parameters remain the same.
[0097] The performance of the solid electrolytes prepared in Examples 1 to 5 and Comparative Examples 1 to 2 was tested:
[0098] (I) Ionic conductivity test: The Autolab PGSTAR302N electrochemical workstation was used to test the AC impedance spectrum of the sample, and the corresponding particle conductivity was calculated according to the formula. Test method: In the glove box, the electrolyte impedance R was indirectly obtained by testing the blocking electrode assembled with stainless steel / composite solid electrolyte / stainless steel. The ionic conductivity was tested at 25°C with a frequency range of 0.1-1MHz and a voltage of 10mV. The ionic conductivity of the electrolyte film can be calculated by the formula: σ=L / (S×R), where L is the thickness of the electrolyte film, in cm, and S is the effective contact area between the electrolyte film and the stainless steel sheet, in cm 2 , R is the impedance of the electrolyte film, in Ω.
[0099] (II) Electrochemical stability window: The electrochemical stability window of the sample was tested using an Autolab PGSTAR302N electrochemical workstation. Test method: In a glove box, a button cell was assembled in the order of anode shell, stainless steel sheet, lithium sheet, composite solid electrolyte, stainless steel sheet, metal shrapnel, and cathode shell, and the linear scanning voltammetric curve of the electrolyte film in the range of 2.5-5V was recorded at a scanning rate of 1mV / s and a test temperature of 25°C.
[0100] (III) Mechanical properties test: The mechanical properties of the electrolyte film were tested using a CMT4104 electronic universal measuring instrument. Test method: The polymer film was cut into long strips and fixed between the clamps of a tensile machine at a stretching rate of 5 mm / min.
[0101] The performance test results are shown in Table 1.
[0102] Table 1
[0103]
[0104]
[0105] The impedance spectrum of the three-dimensional structured ceramic-polymer composite solid electrolyte prepared in Example 1 is as follows Figure 2 The linear sweep voltammetry curve is shown in Figure 3 The stress-strain curve is shown in Figure 4 shown.
[0106] From the above test results, it can be seen that by comparing Example 1 and Comparative Example 1, the embossing process can further improve the ionic conductivity, electrochemical window, mechanical strength and elongation at break of the composite polymer electrolyte. Comparative Example 1 and Comparative Example 2 show that the addition of phenoxy resin can improve the mechanical strength and elongation at break of the material. Examples 2 to 5 show that the electrochemical and mechanical properties of the composite solid electrolyte can be adjusted in a wide range by optimizing the experimental conditions.
[0107] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0108] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A three-dimensional structured ceramic-polymer composite solid electrolyte, characterized in that: including three-dimensional structural ceramics and polymer composites; The three-dimensional structural ceramic is an oxide-type ceramic electrolyte with a three-dimensional structure, and the ceramic electrolyte is one of LLTO ceramic, LLZO ceramic and LATP ceramic; The polymer composite includes a polymer, a lithium salt, nitriles and a phenoxy resin.
2. A three-dimensional structured ceramic-polymer composite solid electrolyte according to claim 1, characterized in that: The polymer includes one or more of polyethylene oxide, polyvinylidene fluoride, polymethyl methacrylate, polyvinylidene fluoride co-hexafluoropropylene, polyurethane acrylate, and polyethylene glycol; and / or, the lithium salt comprises one or two of lithium halide, lithium bis(trifluoromethylsulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate, and lithium tetrafluoroborate; And / or, the nitriles include one or two of succinonitrile, adiponitrile and benzyl cyanide.
3. A method for preparing a three-dimensional structured ceramic-polymer composite solid electrolyte according to any one of claim 1 or claim 2, characterized in that: The following steps are involved: S1: The composite slurry of ceramic electrolyte and epoxy resin is coated to obtain a film with a thickness of 10-100 μm; S2: stamping the adhesive film to obtain a stamped adhesive film; S3: sintering the imprinted film to obtain a three-dimensional structural ceramic; S4: preparing a polymer composite system solution, and blending it with three-dimensional structural ceramics to obtain a three-dimensional structural ceramic-polymer composite solid electrolyte.
4. The method for preparing a three-dimensional structured ceramic-polymer composite solid electrolyte according to claim 3, characterized in that: The mass ratio of the ceramic electrolyte to the epoxy resin in the S1 is (5-15):(2.5-30).
5. The method for preparing a three-dimensional structured ceramic-polymer composite solid electrolyte according to claim 3, characterized in that: The epoxy resin in S1 is a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin, with a mass ratio of (2-20): (0.5-10).
6. The method for preparing a three-dimensional structured ceramic-polymer composite solid electrolyte according to claim 3, characterized in that: In S2, the stamping template is a metal nickel template with regular-shaped protrusions on the surface, and the shapes of the protrusions include but are not limited to hexagons, triangles, quadrilaterals or circles.
7. The method for preparing a three-dimensional structured ceramic-polymer composite solid electrolyte according to claim 6, characterized in that: The height of the protrusions is 10-50 μm, and the pitch between the protrusions is 5-20 μm.
8. The method for preparing a three-dimensional structured ceramic-polymer composite solid electrolyte according to claim 3, characterized in that: In S2, the stamping temperature is 30-100° C., and the stamping speed is 1-20 cm / min.
9. The method for preparing a three-dimensional structured ceramic-polymer composite solid electrolyte according to claim 3, characterized in that: In S3, the sintering temperature is 500-950° C., and the sintering time is 1-10 hours.
10. The method for preparing a three-dimensional structured ceramic-polymer composite solid electrolyte according to claim 3, characterized in that: In S4, the polymer complex system solution is prepared by the following steps: The polymer, lithium salt, nitrile and phenoxy resin are dissolved in a solvent in a mass ratio of (30-50): (10-25): (10-20): (1-5), and mixed evenly to obtain a polymer composite system solution.
Citation Information
Patent Citations
Bionic bioceramic with through-hole structure and preparation method and application thereof
CN104606712A
Ceramic-polymer composite solid electrolyte with three-dimensional skeleton structure as well as preparation method and application of ceramic-polymer composite solid electrolyte
CN111244536A
Three-dimensional composite solid electrolyte and preparation method and application thereof
CN118136926A
METHOD FOR PRODUCING THREE-DIMENSIONAL SOLID ELECTROLYTE STRUCTURES
DE102022108265A1
Polymer composition and composite membrane
JP2005255850A